1853 N.M. Laws 406, An Act Prohibiting the Carrying of Weapons Concealed or Otherwise, § 25 - (:unkn) unknown (General Publisher, 1853)
Prohibited the carrying of a concealed pistol, Bowie knife (cuchillo de cinto), Arkansas toothpick, Spanish dagger, slungshot, or any other deadly weapon.
--
Keywords: CARRY - CONCEALED